Maarak Bungo Lamang - Merry Suhesti; Desfiarni Desfiarni (SENDRATASIK UNP, 2020)
Maarak Bungo Lamang Dance is a result of the creation of dance creations based on the life phenomenon of the Durian River of the South Solok district in order to celebrate the day of the Prophet Maulid. In this regard, the tradition of society that has a sense of gratitude for the day of the Prophet Maulid in a festive way is not separated from the Islamic faith.  The dance work "Maarak Bungo Lamang" is an interpretation of the community tradition of the river Durian in welcoming the Prophet's Maulid by means of a journey around the village along with Shalawat-Shalawat. It is as an expression of gratitude for the Prophet's Maulid day.  The dance works were performed by 7 dancers, 3 male dancers and 4 female dancers as well as 13 Pendukkung dancers for the early dances, expected to be a new form of dance creations. Program artwork is aimed at adding a wealth of dance artwork, as well as an educational platform for new artists.